Multibeam array antenna for base station in the fifth-generation mobile communication system / Intan Izafina Idrus - Intan Izafina , Idrus (2020)
Research on the fifth-generation (5G) mobile communication system has been accelerated to meet the standardization of the International Telecommunications Union for higher data traffic and higher data rates. The main requirements of the 5G mobile communication systems are the utilization of millimeter waves, the deployment of small cells, and the use of multibeam array antennas for multiple-input multiple-output schemes. Multibeam array antennas play an important role in developing a new base station to enhance system capacity, improve network coverage, and reduce co-channel interference. The main objective of this thesis is to design a single-layer multibeam array antenna at 28 GHz for base station in a 5G mobile communication system. The proposed multibeam array antenna is employed with a Butler matrix, which is the most promising solution for a 5G base station antenna. However, the literature has reported issues such as high amplitude imbalance and inaccurate phase differences between the output ports of the Butler matrix that cause the radiation characteristics to show incorrect main beam directions. To overcome these issues, a Butler matrix must have highly accurate dimensions to ensure the main beams point at the desired directions. This thesis presents the design of a multibeam array antenna with eight antenna elements fed by an 8 8 Butler matrix. The Butler matrix consists of sixteen crossovers, twelve quadrature hybrids, and eight phase shifters. The optimum design of each circuit element was obtained to form the 8 8 Butler matrix. A single-element microstrip antenna was designed to operate at 28 GHz. The microstrip antenna was integrated at each output port of the Butler matrix. The complete structure of a multibeam array antenna was simulated and optimized to obtain the desired radiation characteristics. Moreover, the beam coverage of the multibeam array antenna with different antenna spacing in the vertical plane was also studied and analyzed. The results show that the beam coverage was reduced as the antenna spacing increased. Additionally, the appearances of grating lobes were observed when the antenna spacing was increased to 0.7λ. Therefore, the multibeam array antenna with an antenna spacing of 0.6λ was selected for fabrication. The multibeam array antenna was fabricated using a low dielectric constant and low tangent substrate material named NPC-F220A. The results indicate that the 8 8 Butler matrix achieved a low insertion loss and a low phase error with average values of 2 dB and ± 10° at 28 GHz, respectively. The return losses of the multibeam array antenna were less than −10 dB, ranging from 27 GHz to 29 GHz. The main beams of the radiation pattern were pointed at ± 6°, ± 18°, ± 30°, and ± 44° with antenna gains between 9 dBi and 14 dBi. Furthermore, the configurations of multibeam base station antennas to achieve a 360° coverage area in the horizontal plane were presented. The beam coverage designs in the horizontal and vertical sectorizations were analyzed. The findings show that the proposed design concept of multibeam base station antennas is adequate and suitable for a 5G mobile communication system.